Numerical study of Darcy-Forchheimer model with activation energy subject to chemically reactive species and momentum slip of order two - Majeed, A.; Zeeshan, A.; Noori, F. M. (AIP advances, 2019)
This paper addresses the impact of Darcy-Forchheimer flow of MHD viscous fluid over a linear stretchable surface. Inspection has been accomplished in the presence of Arrhenius activation energy, second order slip and chemical reaction which has not been considered earlier. Flow in the porous media is categorized by taking Darcy-Forchheimer model. In addition we considered electrically conducting flow which is induced by stretching sheet. Suitable similarity variables are employed to get the ordinary differential equations (ODE’s). The obtained mathematical expression are now solved numerically with the aid of bvp4c Matlab package which instigated three-stage Lobatto IIIa finite difference collocation procedure. Graphs are developed against convergence parameters like porosity parameter (Kp), local inertia coefficient (Fr) activation energy (E), chemical reaction rate constant (σ), Schmidt number (Sc), temperature difference ratio (Γ), exponentially fitted constant (m), magnetic parameter (M), radiation parameter (R), 1st-order (γ) and 2nd-order (δ) slip parameter, suction or injection parameter (S), Prandtl number (Pr). It is found that Sherwood number decreases in the presence of activation energy while opposite behaviour is seen for temperature difference ratio parameter, whereas temperature profile enhances for large value of inertia parameter and porosity parameter.